Disaster Mitigation in a World Heritage City: BPBD’s Strategy to Deal with Landslides in Sawahlunto, UNESCO Site - Purnama, Tirza Haqia; Putera, Roni Ekha; Koeswara, Hendri (Universitas Teuku Umar, 2025)
This study analyzes the landslide mitigation strategy by the Regional Disaster Management Agency (BPBD) in Sawahlunto, which faces high landslide risks due to steep topography, land use changes, and high rainfall. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The findings show that while BPBD has implemented strategies such as the Disaster Resilient Village program and community socialization, their effectiveness remains limited. Challenges include low community awareness, budget constraints, inadequate infrastructure like early warning systems, and weak coordination among Regional Apparatus Organizations (OPDs). Non structural mitigation is hindered by a lack of public understanding of preventive measures, while structural mitigation faces geographical and resource limitations. This study underscores the need for stronger cross sector collaboration and optimized infrastructure. Key recommendations include establishing a comprehensive early warning system, expanding disaster education programs, and strengthening inter agency coordination. Additionally, increasing budget allocation and integrating technology based solutions can improve mitigation efforts. The impact of this research lies in its contribution to more effective disaster mitigation policies in high risk areas, enhancing community resilience and preparedness. The findings also serve as reference for other cities facing similar challenges, providing insights into best practices for disaster risk management.